Optimization and Tribological Properties of Hybridized Palm Kernel Shell Ash and Nano Boron Nitride Reinforced Aluminium Matrix Composites. (22nd June 2022) - Lokeshwari, M.; Sagar, P. Vidya; Kumar, K. Dilip; Thirupathy, D.; Subbiah, Ram; Ganeshan, P.; Seikh, A. H.; Mohammed, S. M. A. K.; Christopher, David
Abstract : The tribological properties of hybridized reinforced aluminium matrix composites were optimized using Taguchi and Grey Relational Analysis in conjunction with an L16 orthogonal array. The combination of palm kernel shell ash (PKSA) (0–5 wt. %) along with nano BN reinforcements was taken in interest. Loads and speeds (500, 750, 1000, and 1250 rpm) were employed as control parameters for the experiment. Using a Taber type abrasion machine, the wear samples were made, and the wear experiments were carried out. Speed and load were more important than the percentage of reinforcements in composites when it came to evaluating wear index and loss of volume. With respect to wear index and volume loss, Taguchi-relational Grey's analysis identified A3B1C1 (reinforcement = 5  wt. %; load = 500  g; speed = 500  rpm) as the optimal process parameter combination, with a reinforcement of 3 wt. %, load = 500  g, and speed = 500  rpm being the second-best option. Validation tests have revealed that the anticipated and experiment values at the optimal situations are both within the acceptable range. Performance is influenced more by speed than by load, which is influenced more by the weight percentage of composites, as demonstrated by the application of the Taguchi and Grey Relational Analysis methods.